Predictors of Refractoriness and Survival following Transarterial Chemoembolization for Hepatocellular Carcinoma: Outcomes from a Southeast Asian Cohort - Kuhn, Rudolf V.; Ignacio, Glenn Marc G.; Jamias, Jade D.; Teh, Catherine S.C. (Journal of Clinical Interventional Radiology ISVIR, 2022)
Purpose Patients with hepatocellular carcinoma (HCC) become refractory to repeated sessions of transarterial chemoembolization (TACE). The aim of this study was to identify predictors associated with overall survival and refractoriness following repetitive TACE of HCC among patients in Southeast Asia.Methods The clinical and laboratory characteristics and radiologic response of 39 patients treated with conventional TACE (range 2 to 5) with mitomycin from January 2012 to June 2018 were retrospectively analyzed. Patients were mostly male with a median age of 59 years and belonged to the BCLC B stage with a median tumor size of 7.5 cm.Results The median overall survival was 23.2 months and the overall mortality at 5 years was 36%. Multivariate Cox regression analysis revealed that Child–Pugh (CP) score (hazard ratio [HR] = 3.47, p = 0.044), AST (HR = 7.6, p = 0.021), tumor size (HR = 5.47, p = 0.033), progressive disease on Choi criteria (HR = 5.47, confidence interval [CI] 1.15–25.99, p = 0.033), neutrophil-lymphocyte ratio (HR = 1.25, p = 0.049), and nodular enhancement on follow-up computed tomography (CT; HR = 1.98, p = 0.034) were independent risk factors for poor survival. ALT (p = 0.005), enhancement (p = 0.003), CP score (p = 0.010), and progressive disease on Choi criteria (p = 0.022) were predictive of TACE refractoriness/failure.Conclusion Elevated liver enzymes, CP score, and progressive disease on Choi criteria accurately predict TACE refractoriness and failure, allowing early identification of patients who might benefit from other therapies.
Keywords: TACE; liver cancer; response; survival